Real-life analysis of efficacy and safety of everolimus plus exemestane in hormone receptor-positive, human epidermal growth factor receptor-2-negative metastatic breast cancer patients: A Turkish Oncology Group (TOG) study - Bilici, Ahmet; Uysal, Mükremin; Menekşe, Serkan; Akın, Semih; Yıldız, Fatih; Turan, Merve; Sezgin Göksu, Sema; Beypınar, İsmail; Sakalar, Teoman; Değirmenci, Mustafa; Erdem, Dilek; Başaran, Gül; et al. (Taylor & Francis Inc, 2022)
Purpose: This study evaluated the efficacy and safety of everolimus (EVE) plus exemestane (EXE) in hormone-receptor positive (HR+), human epidermal growth factor receptor-2-negative (HER2?) metastatic breast cancer (MBC) patients in real-life settings. Methods: Overall, 204 HR+, HER2? MBC patients treated with EVE + EXE after progressing following prior endocrine treatment were included. Overall survival (OS) and progression-free survival (PFS) and safety data were analyzed. Results: The objective response rate, median PFS, and median OS were 33.4%, 8.9 months, and 23.4 months, respectively. Multivariate analysis revealed that negative progesterone receptor status was a significant determinant of poor treatment response (p = 0.035) and PFS (p = 0.024). The presence of bone-only metastasis was associated with better treatment response (p = 0.002), PFS (p < 0.001), and OS (p = 0.001). Conclusion: We confirmed the favorable efficacy and safety profile of EVE + EXE for HR+, HER ? MBC patients.
Keywords: Everolimus; Exemestane; Metastatic Breast Cancer; Hormone Receptor-Positive; HER Negative; Efficacy